ANALLISIS PERBANDINGAN METODE FUZZY MAMDANI DAN FUZZY TSUKAMOTO DALAM MENGUKUR KEPUASAN PENDUDUK TERHADAP KINERJA PEGAWAI DI NEGERI ALLANG - Upuy, Doms; Saidu , Rusnian Isfahami; Salamena , Gieska Nataly; Juma , Arman; Lopumeten, Jesica; Palembang, Citra Fathia (INDONESIAN JOURNAL ON DATA SCIENCE, 2024)
The aim of this research is to evaluate the level of population satisfaction with employee performance in Allaug State. The Fuzzy Mamdani and Fuzzy Tsukamoto methods are used to process qualitative and quantitative data. This study involved a survey of 100 Allaug State residents, using a questionnaire covering various aspects of public service. The research results show that the Fuzzy Tsukamoto method produces a higher level of population satisfaction compared to the Fuzzy Mamdani method. Further analysis reveals that factors such as service speed, employee friendliness, and procedural efficiency have a significant influence on satisfaction levels. This research also identifies areas that need improvement in public services in Allaug State. The implications of these findings are discussed in the context of improving government service quality and community welfare.